Critical Stylistics in Advertisement of Wardah and Revlon Products - Tri Fitriyani; Rahmadsyah Rangkuti; Umar Mono (ALTSA Publisher, 2022)
This research aimed to analyze types of linguistic meaning in advertisements of Wardah and Revlon products. The data of this research were the words and sentences. The data source was advertisements of Wardah and Revlon products, consisting of fifteen advertisements of Wardah and fifteen of Revlon. The products consisted of lipstick, liquid foundation and mascara. The method used in this research was descriptive qualitative adopted qualitative data analysis procedures proposed by Miles & Huberman (1994), the theory of Stylistics analysis from Jeffries (2016). Types of meaning in Stylistics found in the data linguistic meaning with 528 data. The data is divided into graphology, phonology, and lexical. Graphology is divided into capitalization, punctuation, bold and italic. The total data of graphology gained 281 data. Capitalization is divided into the beginning of a sentence, product name, and descriptive word. The total data of capitalization gained 123 data. Punctuation is divided into full stops, commas, quotation marks, and exclamation marks. The total data of punctuation gained 49 data. Bold and italic gained 101 data. Phonology is divided into alliteration, assonance, and consonance. The total data of phonology is 156 data. Lexical is divided into one – base and a compound. The total data of lexical gained 99 data.